Abiotrophia defectiva as a Rare Causative Agent of Periprosthetic Total Knee Arthroplasty Infections: A Case Report and Literature Review - Kocazeybek, Emre; Demirel, Mehmet; Ersin, Mehmet; Ergin, Omer Naci; Sadic, Betul; Yavuz, Serap Simsek; Asik, Mehmet (Journal of Laboratory Physicians, 2020)
We present a case of Abiotrophia defectiva in a prosthetic knee infection following total knee replacement for the first time. A 69-year-old female was prediagnosed with prosthetic knee infection, and a two-stage revision arthroplasty was applied. A. defectiva was cultured by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) from the synovial fluid aspirates. Penicillin G and gentamicin had been administered. One year postoperatively, a scintigraphy showed no recurrence. A. defectiva may be missed in culture negative patients with knee or hip arthroplasty. They should be carefully evaluated if they have undergone recent dental procedures.
Keywords: Abiotrophia defectiva; osteoarticular infections; MALDI-TOF MS